Reproductive Regulation of PrRPs in Teleost: The Link Between Feeding and Reproduction - Xia, Chuanhui; Qin, Xiangfeng; Zhou, Lingling; Shi, Xuetao; Cai, Tianyi; Xie, Yunyi; Li, Wei; Du, Ruixin; OuYang, Yu; Yin, Zhan; Hu, Guangfu (Frontiers in Endocrinology, 2021)
Prolactin-releasing peptide (PrRP), a sort of vital hypothalamic neuropeptide, was subsequently found exerting an enormous function on the food intake in mammals. However, little is known about the functional role of PrRP in teleost. In the present study, two PrRP isoforms and four PrRP receptors had been isolated from grass carp. Ligand-receptor selectivity displayed that PrRP1 preferentially bind with PrRP-R1a and PrRP-R1b, while PrRP-R2a and PrRP-R2b were special receptor for PrRP2. Tissue distribution indicated that both PrRPs and PrRP-Rs were highly expressed in hypothalamus-pituitary-gonad axis and intestine, suggesting the latent function on food intake and reproduction. Using grass carp as model, we found that food intake could significantly induce hypothalamus PrRP mRNA expression, which suggested that PrRP should be also an anorexigenic peptide in teleost. Interestingly, intraperitoneal (IP) injection of PrRPs could significantly induce serum luteinizing hormone (LH) secretion and pituitary LHβ and GtHα mRNA expression in grass carp. Moreover, using primary culture grass carp pituitary cells as model, we further found that PrRPs could directly induce pituitary LH secretion and synthesis mediated by AC/PKA, PLC/IP3/PKC and Ca2+/CaM/CaMK-II pathways. Finally, estrogen treatment of prepubertal fish elicited increases in PrRPs and PrPR receptors expression in primary cultured grass carp hypothalamus cells, which further confirmed that PrRP/PrRPR system may participate in neuroendocrine control of fish reproduction. These results, taken together, suggested that PrRPs might acted as a coupling factor in feeding metabolism and reproductive activities in teleost.